Desafios e possibilidades do ensino de Ciências/Química em uma escola ribeirinha: investigação temática Freireana e a perspectiva intercultural - Malheiros, Joaquina Barboza (2018)
The presente eassy is the result of a qualitative research was done in order to review in the intercultural perspective the possibilities and challenges according to approach of the Teaching the Nature of Science at High School, in a Riversidade School, located in na island. In the State of Pará. For this purpose, it was sought through: a) To identify some assumptions that underlie or can substantiate the teaching of Natural Sciences, in the perspective of Intercultural Education; b) To analyze the teaching of Natural Sciences, Elementary and High School, proposed in the school, establishing relations with the official guidelines and the scientific productions that base the modality of Education of the Field and the teaching of Natural Sciences; c) To elaborate a didactic sequence based on the proposal of Thematic Research for the teaching of Natural Science, focusing on Teaching Chemistry in the perspective of Intercultural Education. We are based on the assumptions of intercultural education proposed by Walsh (2000) and in the Brazilian context by Fleuri (2003, 2012), approaching Freire's thematic research proposal (2004, 2005, 2006) for the elaboration of the didactic sequence. The research was carried out in a riverside school located in Ilha das Cinzas - the researcher's home - in the municipality of Gurupá, in the Marajó archipelago, State of Pará. The subjects of this research were: two male residents and one female resident of the community, the science teacher, the school coordinator and the high school students, 17 female students and 1 male student. Data were collected through documentary analysis, interviews, observations and elaboration of a didactic sequence. Moreover the interviews with the residents, pedagogical coordinator and the Sciences’ teacher and with the observations, we find this teaching - similar to teaching in the other areas of knowledge in this school - presents several challenges, accordingly with regard to teacher training, times and school spaces and specific didactic materials. With the observations and documental analysis in the Teaching of Natural Sciences, we identified that the proposal of the High School project, more forcefully, does not consider the characteristics and specificities of the population of the riverside community and distance itself from the proposal of the Curricular Guidelines of the Education of the Field. On the basis of this, in search of an education that takes into account the cultural aspects of the community, valuing its knowledge, encouraging this relationship between subjects, promoting the encounter, narrowing these relations, we elaborate a proposal for the Teaching of Natural Sciences / Chemistry, using the thematic research of Freire, starting from the re-reading of intercultural education, as a possibility that is closer to the demands of education in the reality of the riverside school, considering its possibilities and challenges.